Rehabilitation management of postmenopausal osteoporosis associated with degenerative neurological conditions - Roxana Pipernea; Gabriela Dumitrescu; Florina Ligia Popa; Mihaela Stanciu; Mădălina Gabriela Iliescu; Mara Carsote; Claudiu Nistor; Adelina Brescan; Sergiu Brescan; Viorela-Mihaela Ciortea; Laszlo Irsay; Rodica Ungur; et al. (Balneo and PRM Research Journal, 2024)
Background: The evolving association of neurological disorders such as Parkinson's disease (PD) and stroke may aggravate postmenopausal osteoporosis. In this situation, inactivity and lack of movement are the main factors that contribute contribute to exacerbate osteoporosis and the occurrence of osteoporotic fractures. Material and Methods: We present the case of a 62-year-old female patient diagnosed with diffuse postmenopausal osteoporosis, Parkinson's disease, and left frontal ischemic lacuna. 6 months before admission to our rehabilitation clinic, she suffered a trauma by falling that resulted in an L3 vertebral fracture and a right forearm fracture. L2-L4 posterior segmental spinal fusion and right forearm osteosynthesis were per-formed. Postoperatively, a motor deficit was found in the lower limbs. She was diagnosed clin-ically and following neurophysiological investigations with bilateral external popliteal sciatic nerve paresis. In these circumstances, the patient suffered a new trauma, resulting in an open fracture at the same level of the right forearm which also required surgical treatment. Results and discussion: Following the rehabilitation program, the evolution was favorable with im-proved functioning and partial restoration of walking. Conclusion: The association of degener-ative neurological and bone metabolic diseases in this case led to significant disability, making the rehabilitation process more challenging.